Antibody-engineered nanoparticles selectively inhibit mesenchymal cells isolated from patients with chronic lung allograft dysfunction. (2015) - Cova, Emanuela; Colombo, Miriam; Inghilleri, Simona; Morosini, Monica; Miserere, Simona; Peñaranda-Avila, Jesus; Santini, Benedetta; Piloni, Davide; Magni, Sara; Gramatica, Furio; Prosperi, Davide; Meloni, Federica
Aims: Chronic lung allograft dysfunction represents the main cause of death after lung transplantation, and so far there is no effective therapy. Mesenchymal cells (MCs) are primarily responsible for fibrous obliteration of small airways typical of chronic lung allograft dysfunction. Here, we engineered gold nanoparticles containing a drug in the hydrophobic section to inhibit MCs, and exposing on the outer hydrophilic surface a monoclonal antibody targeting a MC-specific marker (half-chain gold nanoparticles with everolimus).Materials & methods: Half-chain gold nanoparticles with everolimus have been synthesized and incubated with MCs to evaluate the effect on proliferation and apoptosis.Results & discussion: Drug-loaded gold nanoparticles coated with the specific antibody were able to inhibit proliferation and induce apoptosis without stimulating an inflammatory response, as assessed by in vitro experiments.Conclusion: These findings demonstrate the effectiveness of our nanoparticles in inhibiting MCs and open new perspectives for a local treatment of chronic lung allograft dysfunction. Original submitted 24 July 2013; Revised submitted 15 October 2013